2018
DOI: 10.1159/000492616
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and Cardiac Arrhythmia: A Literature Review

Abstract: Objective: One of the most important side effects of opioids is their influence on the electrical activity of the heart. This review focusses on the effects of opioids on QT interval prolongation and their arrhythmogenic liability. Methods: By using various keywords, papers published up to 2018 in different databases were searched and identified. The search terms were opioids names, corrected QT interval, human-ether-a-go-go gene, torsades de pointes (TdP), cardiac arrhythmias, opioid dependence and other rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 125 publications
(142 reference statements)
2
94
0
3
Order By: Relevance
“…Opium contains 80 different alkaloids, such as morphine and codeine. Morphine is a μ receptor agonist responsible for cardiovascular complications, including histamine release, and results in bradycardia, vasodilation, hypotension, and decreased cardiac output [94]. It has also been demonstrated that increased contractile response due to the stimulation of rat cardiac betaadrenergic receptors is reversed through delta receptor agonism [95].…”
Section: Potential Mechanismmentioning
confidence: 99%
“…Opium contains 80 different alkaloids, such as morphine and codeine. Morphine is a μ receptor agonist responsible for cardiovascular complications, including histamine release, and results in bradycardia, vasodilation, hypotension, and decreased cardiac output [94]. It has also been demonstrated that increased contractile response due to the stimulation of rat cardiac betaadrenergic receptors is reversed through delta receptor agonism [95].…”
Section: Potential Mechanismmentioning
confidence: 99%
“…13,[17][18][19] The association between opioids and cardiovascular (CVD) outcomes has not been widely reported and results have been mixed. 2,16,24,25 In a recent study among those ages ‡45 years using subgroups of opioids, no significant association was evident between opioid medication use and coronary artery disease. 25 A 2007 review summarizing the use of tramadol for management of chronic pain indicated that tramadol had no known associations with CVD adverse effects, gastrointestinal bleeding, or renal toxicity in contrast to contraindications associated with chronic NSAIDs.…”
Section: Introductionmentioning
confidence: 97%
“…There are many side effects of opioids 41 and one of the most common effects on the cardiovascular system is prolongation of the QT interval which can lead to torsade de pointes (TDP), kind of the ventricular tachyarrhythmia that can provokes sudden death. 42,43 The other side effects on the cardiovascular system are bradycardia, histamine release, and rhythm disturbance. Mechanism of action of prolongation of QT interval is associated with prolonged cardiac repolarisation that is initiated by rapid outflow of potassium (K+), through the cardiac rapid-rectifying K+ channel.…”
Section: Resultsmentioning
confidence: 99%